2014
DOI: 10.1093/europace/euu011
|View full text |Cite
|
Sign up to set email alerts
|

His or para-His pacing preserves left ventricular function in atrioventricular block: a double-blind, randomized, crossover study

Abstract: His or para-His pacing preserves LVEF and mechanical synchrony as compared with RVSP after 12 months pacing in patients with AVB, narrow QRS, and LVEF > 0.40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 25 publications
2
108
1
3
Order By: Relevance
“…Acute lead dislodgment is uncommon but a significant increase in threshold has been reported in up to 5% of cases postimplant requiring lead revision . Initially success rates of capturing the true HB were of the order of 80 to 85% but more recent improvements in leads and delivery systems and in implanter experience have increased this to in excess of 90% …”
Section: His Bundle Pacingmentioning
confidence: 99%
“…Acute lead dislodgment is uncommon but a significant increase in threshold has been reported in up to 5% of cases postimplant requiring lead revision . Initially success rates of capturing the true HB were of the order of 80 to 85% but more recent improvements in leads and delivery systems and in implanter experience have increased this to in excess of 90% …”
Section: His Bundle Pacingmentioning
confidence: 99%
“…Hisian (pacing the His Bundle) and Para-hisian (pacing the myocardium around the His bundle) pacing although restores the normal electrical activation pattern, it is technically difficult and has problems with higher pacing thresholds. 16,17 RVOT pacing has been studied and compared with RVA pacing in multiple trials with most of them favoring non-apical pacing sites. A metaanalysis of 14 randomized controlled trials with more than 700 patients showed higher left ventricular ejection fraction (LVEF) with non-apical pacing site.…”
Section: Why Rv Apical Pacing Is Deleterious To Cardiac Function?mentioning
confidence: 99%
“…Some data from acute or short-term randomized studies support this hypothesis. [34][35][36][37] Most studies have used LVEF as a surrogate of clinical outcomes. The majority of studies have reported a preservation of LVEF with alternate site RV pacing when compared with reduced LVEF in those randomized to RV apical pacing.…”
Section: Alternative Rv Pacing Sitesmentioning
confidence: 99%
“…Although promising, pacing from sites in the His bundle region remains problematic with lower success rates, higher pacing thresholds, and longer procedure times. 35,37 Alternative RV pacing sites have not yet been shown to reduce significant cardiovascular events, such as AF or HF. One additional randomized clinical trial comparing septal locations with RV apical pacing is completing follow-up and when reported may provide valuable additional insights as to the clinical value of these alternate pacing sites.…”
Section: Alternative Rv Pacing Sitesmentioning
confidence: 99%